(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article reflects on the performative theatrical act and the co-occurrence of verbal and non-verbal semiosis in aphasia contexts. My focus is on the reconstitution of multimodal semiosis by aphasia, not in the absence of aphasia, but in the presence of aphasia. From there, I investigated the notion of modal density of the semiosis that are interconnected, aiming to emphasize that they are: distinct; that its relevance in the construction of meaning depends on the multimodal resource, on the oral and motor capacity of the aphasic, on the most summoned and recurrent resources in the scene, on the context of meaning production. This article deepens theoretical, aesthetic, methodological and practical interests about performative staging with aphasic people in order to develop a field of study that contributes to the practices and pedagogies of creation in the performing arts.